Effects of Mg2+, Ni2+ and Ca2+ on ATP binding kinetics of nicotinate nucleotide adenylyltransferase from Klebsiella pneumoniae and Enterococcus faecium: insights from empirical and computational studies - Van Deventer, Ruan (University of the Witwatersrand, Johannesburg, 2023)
NNAT is an attractive target for drug development due to its crucial role in NAD+ synthesis. However, its characterisation in ESKAPE species, such as Klebsiella pneumoniae and Enterococcus faecium, remains limited. This study aimed to elucidate the binding mechanism of ATP, a pivotal substrate, to these NNAT species, focusing on the role of divalent metal ion cofactors. KpNNAT and EfNNAT enzymes were overexpressed and purified, yielding approximately 2 mg/ml for both. Various techniques were employed to investigate their properties, including far-UV CD, extrinsic ANS fluorescence, stopped-flow kinetic analyses, and MD simulations. The results revealed that KpNNAT could bind ATP independently of divalent metal ions, but catalytic activity required the presence of Mg2+. The kinetic analysis showed ka values of 5.99 μM-1 .sec-1 without divalent metal ions and 5.72 μM-1 .sec-1 in the presence of Mg2+. The "pseudo"-specific activity values were 0.005 μmol/min/mg without divalent metal ions and 0.374 μmol/min/mg in the presence of Mg2+. Conversely, recombinant EfNNAT exhibited limited ATP association, and the reasons for this remain unclear. Overall, this study shed light on the structural dynamics and functional kinetics of ATP association in both NNAT species. The findings contribute to our understanding of this druggable target and provide insights into the inactivity of EfNNAT, which warrants further investigation.
A dissertation submitted in fulfilment of the requirements for the degree Mater of Science in Biochemistry & Cell Biology, to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: ESKAPE; Computational modeling; Biochemistry; Recombinant protein; Stopped-flow kinetics; NNAT; ATP; Klebsiella pneumoniae; Enterococus faecium; Mant-ATP; Molecular dynamics; UCTD; SDG-3: Good health and well-being